2017
DOI: 10.3748/wjg.v23.i13.2346
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for difficult cecal insertion in colonoscopy: The impact of obesity indices

Abstract: AIMTo identify the factors influencing cecal insertion time (CIT) and to evaluate the effect of obesity indices on CIT.METHODSWe retrospectively reviewed the data for participants who received both colonoscopy and abdominal computed tomography (CT) from February 2008 to May 2008 as part of a comprehensive health screening program. Age, gender, obesity indices [body mass index (BMI), waist-to-hip circumference ratio (WHR), waist circumference (WC), visceral adipose tissue (VAT) volume and subcutaneous adipose t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 32 publications
1
24
1
Order By: Relevance
“…Lower VAT (VAT < 75 cm 2 ) had impact on both the ease of colonoscopy and longer CIT. This result is consistent with former reports demonstrating that lower VAT was significantly associated with longer CIT [ 21 23 ], since higher VAT might provide resistance and help prevent looping. However, to our surprise, the multivariate analysis also demonstrated that higher VAT (150 cm 2 ≤ VAT) caused difficult colonoscopy and longer CIT.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Lower VAT (VAT < 75 cm 2 ) had impact on both the ease of colonoscopy and longer CIT. This result is consistent with former reports demonstrating that lower VAT was significantly associated with longer CIT [ 21 23 ], since higher VAT might provide resistance and help prevent looping. However, to our surprise, the multivariate analysis also demonstrated that higher VAT (150 cm 2 ≤ VAT) caused difficult colonoscopy and longer CIT.…”
Section: Discussionsupporting
confidence: 93%
“…Visceral fat may help prevent looping formation, as those with higher BMI may have more fat, so that the colonoscope could reach the cecum more easily [ 6 ]. However, only a few recent studies have assessed the effect of VAT on difficult colonoscopy [ 21 23 ]. In the present study, lower BMI (BMI < 21 kg/m 2 ) was related to longer CIT during univariate analysis, but its effect disappeared in multivariate analysis, when another obesity index (VAT) was considered simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were recruited from December 2017 to September 2018. Having a lower or higher body mass index (BMI) was reported to be indicative of longer cecal intubation time (CIT) . Eligible patients aged 20–80 years with BMI ≥25 kg/m 2 or <18.5 kg/m 2 and/or previous CIT ≥8 min were enrolled.…”
Section: Methodsmentioning
confidence: 99%
“…Incomplete colonoscopies should be avoided, since patients in this context present an important prevalence of lesions that escape examination . Most patients with a prior incomplete colonoscopy can be colonoscoped successfully, using a variety of scopes, colonoscopy methods and additional equipment …”
Section: Introductionmentioning
confidence: 99%
“…3 Most patients with a prior incomplete colonoscopy can be colonoscoped successfully, using a variety of scopes, colonoscopy methods and additional equipment. 1,[7][8][9] Difficult colonoscopy may be conditioned by patient factors and endoscopist/team related factors (Table 1). 1,[7][8][9] The normal colon has two areas of full fixation (ascending and descending colon), two of partial fixation (cecum and rectum), two ligamentous attachments (splenic flexure and hepatic flexure) and two areas with independent mesenteries (intraperitoneal segments: sigmoid and transverse colon).…”
Section: Introductionmentioning
confidence: 99%